Socializmo propaguotojo Karolio Rutkaus leidybinė veikla JAV 1905–1910 m. - Gargasaitė, Dalia (Knygotyra, 1995)
The article describes one of the founders of the Lithuanian Socialists’ Union in USA (1905), book publisher K. Rutkus. By the year 1904 he has already produced, translated an issued 6 publications. During the period 1905–1910 he has published 9 books and proclamations that he himself prepared and translated. In 1910, since he became an owner of a small printing house, he started as an independent publisher, look up publishing the periodical “Teisybė” (1910–1913) and other books of socialist contents.